Estimation of kidney function in Graves’ disease using creatinine and cystatin C - Sorena Abbaszadeh; Martin H Lundqvist; Östen Ljunggren; Anders Olof Larsson; Maria K Svensson; Selwan Khamisi (Endocrine Connections)
Introduction: There is no consensus regarding methods to estimate kidney function in hyperthyroidism. The aim was therefore to assess changes in filtration markers in patients with Graves’ disease undergoing treatment with antithyroid drugs. Methods: Thirty patients with de novo Graves’ disease were included. Blood sampling, including thyroid-stimulating hormone, fT3, fT4 and creatinine, was performed at baseline, 6 weeks, 3, 6, 12 and 24 months. Cystatin C was measured from frozen samples. To calculate creatinine- and cystatin C-based eGFR, the Lund–Malmö equation (LMR) and the CAPA formula were used. Results: fT3 and fT4 normalized during treatment. Creatinine increased initially but stabilized after 6 months. eGFRLMR decreased until 12 months. Cystatin C decreased, while eGFRCAPA and eGFRCAPA/eGFRLMR increased until 6 months. The mean of eGFRLMR and eGFRCAPA remained stable. The % changes in creatinine and cystatin C were associated with % changes in fT3 and fT4. In regression models including fT3 or fT4 with body weight (all % change), fT3 and fT4 were the strongest predictors of percentual changes in both creatinine and cystatin C. Conclusion: The increase in creatinine and decrease in cystatin C during the treatment of Graves’ disease was significantly associated with changes in thyroid hormones, and for creatinine, also body weight. The mean of eGFRLMR and eGFRCAPA remained stable, suggesting that creatinine and cystatin C were affected by different non-GFR-related factors. The potential use of eGFRLMR and eGFRCAPA to assess kidney function in patients with thyroid disorders should be further evaluated in studies measuring kidney function with state-of-the-art methods.